The use of ADDIE model for designing blended learning application at vocational colleges in Malaysia - Muhamad Azhar Stapa; Nazeri Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2019)
Teaching is a highly complex occupation, which needs to adapt to a great deal of variety in context, subject matter and learners. It does not lend itself to broad generalization. However, academic knowledge is not the only kind of knowledge that is important in today's society, and as teachers we have to be aware of other forms of knowledge and their potential importance to our students, and make sure that we are providing the full range of contents and skills needed for students in a digital age. E-learning strategies are still not explored extensively in the system of vocational education for the learning process in Malaysia. Nevertheless it i possible to provide guidelines or principles based on best practices, theory and research, which must then be adapted or modified to local conditions. This study discusses the instructional design and development of e-Iearning prototype called Vocational Learning (Voc-Learning) by using ADDIE model and implemented via blended learning method. ADDIE model is one of the instructional design models used by many researchers to develop software or applications related to the field of education.The design of application development based on the ADDIE is explained as Analysis, Design, Development, Implementation and Evaluation. The strength of concerned is according to the variables have been devided into several items such as; teaching design, content, user controls and technical. Implementation phase involves formative evaluation of a prototype developed and make adjustments and improvements where necessary. The percentage of expert approval percentage becomes a benchmark in comparison. This study highlights the development of blended Voc-Learning model based on the relevant theories of teaching and learning.